Economic Impact of Adherence to Pain Treatment Guidelines in Chronic Pain Patients. Issue 10 (29th April 2019) - Margolis, Jay M; Princic, Nicole; Smith, David M; Abraham, Lucy; Cappelleri, Joseph C; Shah, Sonali N; Park, Peter W
Abstract: Objectives: This research compared health care resource use (HCRU) and costs for pharmacotherapy prescribing that was adherent vs nonadherent to published pain management guidelines. Conditions included osteoarthritis (OA) and gout (GT) for nociceptive/inflammatory pain, painful diabetic peripheral neuropathy (pDPN) and post-herpetic neuralgia (PHN) for neuropathic pain, and fibromyalgia (FM) for sensory hypersensitivity pain. Methods: This retrospective cohort study used claims from MarketScan Commercial and Medicare Databases identifying adults newly diagnosed with OA, GT, pDPN, PHN, or FM during July 1, 2006, to June 30, 2013, with 12-month continuous coverage before and after initial (index) diagnosis. Patients were grouped according to their pharmacotherapy pattern as adherent, nonadherent, or "unsure" according to published pain management guidelines using a claims-based algorithm. Adherent and nonadherent populations were compared descriptively and using multivariate statistical analyses for controlling bias. Results: Final cohort sizes were 441, 465 OA, 76, 361 GT, 10, 645 pDPN, 4, 010 PHN, and 150, 321 FM, with adherence to guidelines found in 51.1% of OA, 25% of GT, 59.5% of pDPN, 54.9% of PHN, and 33.5% of FM. Adherent cohorts had significantly ( P  < 0.05) fewer emergency department (ED) visits and lower proportions with hospitalizations or ED visits. Mean health care costs increased following diagnosis across all conditions; however, adherent cohorts had significantly lower increases in adjusted costs pre-index to postindex (OA $5, 286 vs $9, 532; GT $3, 631 vs $7, 873; pDPN $9, 578 vs $16, 337; PHN $2, 975 vs $5, 146; FM $2, 911 vs $3, 708; all P  < 0.001; adherent vs nonadherent, respectively). Conclusions: Adherence to pain management guidelines was associated with significantly lower HCRU and costs compared with nonadherence to guidelines.